Superconducting State 2013
DOI: 10.1093/acprof:oso/9780199652556.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous superconductivity and the “pseudogap” state of novel superconductors

Abstract: Novel superconducting compounds such as the high T c oxides are intrinsically inhomogeneous systems. An inhomogeneous structure is created by doping and the statistical nature of the distribution of dopants. Consequently, the critical temperature is spatially dependent: T c ≡ T c (r).Pair-breaking leads to a depression of T c and is a major factor leading to inhomogeneity . The "pseudogap" state is characterized by several energy scales : T*, T c *, and T c ≡ T c res. . The highest energy scale (T*) correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Our quantitative results should be tested against theories of composite, granular superconductors proposed for cuprates (10,14,15,25,(30)(31)(32)(55)(56)(57)(58)(59)(60)(61)(62). The X-ray data indicate that these theories must take into account not only the usual superconducting proximity effects, but also the effects of the strains the two components exert on each other.…”
Section: Discussionmentioning
confidence: 91%
“…Our quantitative results should be tested against theories of composite, granular superconductors proposed for cuprates (10,14,15,25,(30)(31)(32)(55)(56)(57)(58)(59)(60)(61)(62). The X-ray data indicate that these theories must take into account not only the usual superconducting proximity effects, but also the effects of the strains the two components exert on each other.…”
Section: Discussionmentioning
confidence: 91%
“…Defects, as mobile oxygen interstitials, can control electronic inhomogeneity891011121314 and complex multi-scale phase separation15161718192021222324. Furthermore, inhomogeneity in the form of stripes have been shown to induce “shape resonances”2223 in the superconducting gaps in a multi-band superconductor24, which are type of Fano-Feshbach resonances at a BEC-BCS crossover.…”
mentioning
confidence: 99%
“…In high temperature superconductors (HTS), these networks of defects can influence essential properties such as the Fermi surface, pseudogap energy, spin density waves, charge density waves, and even the superconducting critical temperature. The strong tendency towards complex phase separation1415161718192021222324 can be used as advantage for developing new electronic devices. In fact, in some circumstances, defects order can be manipulated by scanning tunneling microscopy (STM)11, and/or by continuously exposing the sample to a UV or X-ray beam6710.…”
mentioning
confidence: 99%
“…The notion that competition between phases with charge ordering, spin ordering and superconductivity results in the formation of complex, heterogeneous structures, arranged as self-organised, fluctuating networks of "superstripes", has grown in popularity, fuelled by experimental evidence taken from a wide range of cuprate superconductors [2,3]. Intrinsic inhomogeneity resulting in phase separation is believed to be at the root of understanding the puzzling "pseudogap" state of underdoped cuprate superconductors above Tc [4]. It is found that in some regions of the material, Cooper pair formation occurs above the resistive transition temperature (Tc) as disconnected "puddles", leading to an anomalous diamag-netic signal.…”
Section: Introductionmentioning
confidence: 99%